The geographical distribution of the soft drink and healthy water industry in AL-Karaada AL-Sharqiya Area - Drjal Ghntab, Yasir Majid; AL-Hiti, Salam Khamees Gharbi (Al-Adab Journal, 2020)
The study of the industrial phenomenon reveals the importance, role and factors of the industrial settlement that contributed to the spread of the industry within the spatial space to show its importance and the extent of the impact of the factors on its spatial distribution. Currently, the study showed that the market factor was the most influential in the signing of establishments at their current locations, as its impact ratio reached (39%), which makes it ranked first among the factors affecting the spatial distribution of the industry. The study also revealed that there are (27) establishments for the manufacture of soft drinks and healthy water in the Eastern Karrada region (48.1%) of which were concentrated in the industrial zone within Zaafaraniya according to the number of establishments index. As for the index of the number of workers in the industrial branch, it recorded the highest percentage as well within the region Industrial in Zaafaraniya, at a rate of (81.6%) of workers in the beverage and water industry by (1646) workers, while the highest percentage of annual workers ’wages within the Industrial Zone in Zaafaraniya increased by (91.1%) by (20642) million dinars from the value of annual workers’ wages within The same industrial branch. With the lowest percentage recorded in terms of the mentioned indicators within the university district in which there is one facility for the beverage and water industry, with a number of employees of (25) workers and an annual wage value of (140) million dinars annually.